Hepatic resection vs percutaneous radiofrequency ablation of hepatocellular carcinoma abutting right diaphragm - Song, Kyoung Doo (World J Gastrointest Oncol, 2019)
BACKGROUND: It is usually difficult to adequately conduct percutaneous ultrasound-guided radiofrequency (RF) ablation for hepatocellular carcinomas (HCCs) abutting the diaphragm. Our hypothesis was that the subphrenic location of HCC could have an effect on the long-term therapeutic outcomes after hepatic resection and RF ablation. AIM: To compare the long-term therapeutic outcomes of hepatic resection and percutaneous RF ablation for HCCs abutting the diaphragm. METHODS: A total of 143 Child-Pugh class A patients who had undergone hepatic resection (n = 80) or percutaneous ultrasound-guided RF ablation (n = 63) for an HCC (≤ 3 cm) abutting the right diaphragm were included. Cumulative local tumor progression (LTP), cumulative intrahepatic distant recurrence (IDR), disease-free survival (DFS), and overall survival (OS) rates were estimated. Prognostic factors for DFS and OS were analyzed. Complications were evaluated. RESULTS: The cumulative IDR rate, DFS rate, and OS rate for the hepatic resection group and RF ablation group at 5 years were “35.9% vs 65.8%”, “64.1% vs 18.3%”, and “88.4% vs 68.7%”, respectively. Hepatic resection was an independent prognostic factor for DFS (P ≤ 0.001; hazard ratio, 0.352; 95%CI: 0.205, 0.605; with RF ablation as the reference category); however, treatment modality was not an independent prognostic factor for OS. The LTP rate was 46.6% at 5 years for the RF ablation group. The major complication rate was not significantly different between the groups (P = 0.630). The rate of occurrence of peritoneal seeding was higher in the RF ablation group (1.3% vs 9.5%, P = 0.044). CONCLUSION: Although OS was not significantly different between patients who had gone hepatic resection or percutaneous RF ablation for HCCs abutting the diaphragm, DFS was better in the hepatic resection group.